تأثير الصدأ على إجهاد التماسك في البيتون المسلح - تريكية علي; منصور نزيه; آل الفضل الشريفة بهيجة (Latakia University Journal -Engineering Sciences Series, 2019)
إن الخسائر الاقتصادية الكبيرة ، التي يسببها تآكل الفولاذ في البيتون المسلح، قد جعلت منه المشكلة الأكبر للبنية التحتية في كثير من الدول، وقد درس الكثير من الباحثين، الدور الضار الذي يسببه تآكل فولاذ التسليح على ديمومة المنشآت البيتونية المسلحة. حالما تصل شوارد الكلوريد إلى مستوى قضيب التسليح ، فإنها تزيل سلبيته عن طريق التحطيم الموضعي للطبقة الحامية السلبية التي تتشكل نتيجة القلوية العالية للخرسانة ( PH 13) . و بعد بدء عملية التآكل ، يشغل تجمع نواتج التآكل ( أكاسيد وهيدروكسيدات حديد ) حجماً أكبر بعدة مرات من حجم الحديد الأصلي ، مما يسبب نشوء اجهادات داخلية تؤدي إلى تشقق وتشظي الغطاء الخرساني . يهدف البحث إلى دراسة تأثير الصدأ على إجهاد التماسك لفولاذ التسليح في المنشآت البيتونية في الساحل السوري عن طريق إجراء اختبار تماسك وطريقة إجراء اختبار تجارب شد مباشر واختبار التآكل المسرع عن طريق تغلغل الكلوريدات فيها. وإجراء اختبار تماسك عن طريق تجربة الشد المباشر على عينات تعرضت للصدأ خلال عملية تغلغل الكلوريدات فيها وذلك من أجل قياس إجهاد التماسك. تمت دراسة كل من المتغيرات ( مقاومة البيتون – أقطار وأشكال قضبان التسليح – عملية تطويق القضبان) في العينات الصحيحة والمخربة. The large economic losses caused by the corrosion of steel in reinforced concrete makes it the largest infrastructure problem for a lot of countries. A lot of researchers have been studying the harmful role which the corrosion of reinforced concrete practices on the durability of reinforced concrete. Once chloride have reached bar level, they depassivate the embodied steel by locally breaking down the passive protective layer formed due to the high alkalinity of concrete pore solution ( PH 13). After initiation of the corrosion process, the accumulation of corrosion products (iron oxides and hydroxides) , occupying a volume several times larger than of the original iron, leads to internal stresses that result in cracking and spalling of the concrete cover. The research aims to study the effect of corrosion on reinforced concrete bond stress in reinforced concrete structures on the Syrian coast by performing bond experiments and the way of performing direct tensioned experiments and accelerated corrosion test through chloride access, and by performing the bond test through direct tensioned experiment on specimens exposed to rust with chloride access procedure in order to measure the bond stress. All the following changes (concrete resistance, diameters and shapes of reinforced bonding bars- stirrup around the bars) in good and corrupted specimens are studied.